Experimental study of cooperation in behavior analysis: Seeking to integrate learning, evolution and development (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
This study reports a bibliographic survey of cooperation studies conducted a) to identify how this phenomenonis characterized and studied in different areas and b) how the study of cooperation can be related to areas ofdevelopment and evolution and analysis behavior. The selection of the studies was performed in two steps. Inthe first step, the main Behavior Analysis journals were selected; and, in the second step, a bibliographicsearch was carried out in five databases with content related to the topic of cooperation. After the exclusioncriterion, 41 articles were analyzed from the analysis categories proposed in the study. It can be concludedthat the study of cooperation includes the characterization and investigation of different behavioralphenomena, most of them possible to be characterized by the concepts of contingency, control of stimulus andsocial reinforcement. The main contribution of this study is to encourage concepts of behavior analysis to beintegrated into the wide discussion scenario on cooperation, especially those carried out in the areas ofdevelopment and evolution of human behavior.
Keywords: cooperation; experimental analysis of behavior; learning; evolution; development